2020
DOI: 10.1111/obr.13150
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adult behavioural weight management interventions on mental health: A systematic review and meta‐analysis

Abstract: Summary There is good evidence that behavioural weight management interventions improve physical health; however, the impact on mental health remains unclear. We evaluated the impact of behavioural weight management interventions on mental health‐related outcomes in adults with overweight or obesity at intervention‐end and 12 months from baseline. Eligible studies were randomized controlled trials (RCTs) or cluster RCTs of adult behavioural weight loss interventions reporting affect, anxiety, binge eating, bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 82 publications
(436 reference statements)
4
43
1
Order By: Relevance
“…Though concerns regarding promotion of diet culture in weight‐loss interventions have an important role in the discussion on weight management, these interventions that have been shown to improve general mood and decrease psychopathology are distinct from restrictive, disordered dieting that may be inaccurately associated with such therapies (70). This aligns with research in adults as well (71), as a recent meta‐analysis found an overall improvement in mental health outcomes following weight‐management interventions (72). However, the longest study to assess this issue was 2 years following treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Though concerns regarding promotion of diet culture in weight‐loss interventions have an important role in the discussion on weight management, these interventions that have been shown to improve general mood and decrease psychopathology are distinct from restrictive, disordered dieting that may be inaccurately associated with such therapies (70). This aligns with research in adults as well (71), as a recent meta‐analysis found an overall improvement in mental health outcomes following weight‐management interventions (72). However, the longest study to assess this issue was 2 years following treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Adolescents may find it difficult to assess whether their food intake is objectively large, possibly leading to overreporting of OBEs (68). (72). However, the longest study to assess this issue was 2 years following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular dysfunction might be at least partly reversible through weight loss and exercise (23). Recent meta-analyses suggest that exercise and weight loss interventions have a beneficial effect on depressive symptoms across a wide age range, including older individuals (106,107). To what extent any effects of these interventions are mediated by improvement of microvascular function remains to be elucidated.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…This study contributes to research on happiness and its correlates in obese individuals . While weight loss has been associated with some benefits in terms of mental health and psychological well-being (Jones et al, 2020), adhering to the MedDiet could become an ecological approach to improve the affective experience and life evaluation of the population, particularly individuals who are overweight and obese, entailing benefits for and beyond happiness. Public policy programs to encourage healthy eating can stress that happiness gains from healthy eating may occur much more quickly than any long-distance improvement to people's physical health (Conner et al, 2015(Conner et al, , 2017Ford et al, 2013;McMillan et al, 2011;Mujcic & Oswald, 2016;White et al, 2013).…”
Section: Discussionmentioning
confidence: 99%